Hot deformation characteristics of hot extruded FGH95 superalloys - DUAN Jiping; TANG Xianglin; SHENG Junying; PENG Zichao; WANG Xuqing; ZOU Jinwen (Fenmo yejin jishu)
The thermal compression deformation behaviors of the hot extruded (HEX) FGH95 alloys were investigated systematically using the Gleeble 3800D thermal-mechanical simulator in the strain rate of 0.001~1.000 s−1 at the deformation temperature range of 1050~1120 ℃. The constitutive equations of the hot extruded FGH95 alloys were derived from the stress-strain curves obtained in the isothermal compression tests. Furthermore, the hot processing maps were established based on the dynamic models. In the results, the corresponding material constants of the constitutive equation are determined as Q=300.925 kJ·mol−1, α=0.01139 MPa−1, and n=1.86. Compared with the hot isostatic pressing (HIP) alloys, the activation energy of the hot extruded FGH95 alloys is declined by more than 50%. According to the energy dissipation efficiency and the microstructure analysis of the hot extruded FGH95 alloys, the processing safety zone and instability zone are identified during the hot extrusion process. Ultimately, the optimal processing conditions of the FGH95 alloys are proposed as the strain rate of 0.010~0.100 s−1 and the deformation temperature of 1050~1120 ℃.